Advantages and limitations of nanoparticle labeling for early diagnosis of infection. (2nd August 2016) - Laurentius, Lars B.; Owens, Nicholas A.; Park, Jooneon; Crawford, Alexis C.; Porter, Marc D.
ABSTRACT: Introduction : Nanoparticle-based disease diagnostics harness a range of unique physical and chemical phenomena for the detection of biomarkers at exceedingly low levels. This capability potentially enables the diagnosis of disease earlier in its progression and improves the likelihood of positive treatment outcomes. This review highlights recent work in this area, and then projects the next steps needed to move this emerging capability beyond the research laboratory. Areas covered : This review examines the advantages and limitations of in vitro health care diagnostic tests that utilize nanoparticles (e.g. noble metal, quantum dot, and magnetic). It includes a brief overview of their unique properties, syntheses, and applicable readout strategies. This is followed by a brief synopsis of the obstacles faced when attempting to translate nanoparticle-based diagnostics from the R&D laboratory to the clinic and other arenas (i.e. the difficulties common to in vitro diagnostics), and then by a much more in-depth examination of the need to control and characterize a range of nanoparticle properties (e.g. size, shape, surface composition, and stability) when making this transition. Expert commentary : The review wraps up with a short commentary and perspective for the next five years, focusing on possible guidelines for nanoparticle characterization.